The State of Sustainable Markets 2019 - International Trade Centre (United Nations, 2019)
This fourth global report provides new insights into the evolution of certified agriculture and forestry. It shows significant growth in sustainability markets. It shows how ITC is supporting “good trade” that contributes to environmental and social sustainability for producers and consumers by teamming up once again with the Research Institute of Organic Agriculture and the International Institute for Sustainable Development to provide data about 14 major sustainability standards for bananas, cocoa, coffee, cotton, oil palm, soybeans, sugarcane, tea and forestry products. Each product also features serious sustainability challenges: child labour, water scarcity, workers’ rights, use of chemicals, etc. The report provides transparency by summarizing those challenges, and by showing which standards initiatives are gaining traction – thus helping to address major societal problems. It also helps shape decisions of policymakers, producers and businesses, working to address systemic labour and environmental challenges through certified sustainable production.